The national security argument for protection of domestic industries. Issue 4 (2nd October 2019) - Cheng, Leonard K.; Whitten, Gregory W.; Hua, Jingbo
ABSTRACT: Tracing the origin of the national security argument for protection of domestic industries to Adam Smith, Alexander Hamilton, and Friedrich List, we study its post-GATT applications with reference to Article XXI of the WTO and highlight some recent abuses. We compare the use of tariff, production/input subsidy, and government procurement as alternative instruments of protection from the perspective of economic efficiency and study the disapproval of inward FDI to gain insights into the underlying national security concerns. The case studies of a) the US tariffs on aluminum and steel, b) German disapproval of the acquisition of a technology firm Leifeld Metal Spinning by a Chinese firm, and c) US' all out global effort to cripple China's telecom equipment giant Huawei are presented for illustration.